Lethality or improved growth as a result of interaction in DNA repair double mutants of Aspergillus - E. Käfer; S.-K. Chae (Fungal Genetics Reports, 1994)
Genetic analysis recently identified nine new DNA repair genes of Aspergillus nidulans, musK - musS, which map on several different chromosomes (Käfer 1994, preceding article in this Newsletter). Such mus mutants are sensitive to certain chemical mutagens, but not sensitive or only slightly sensitive to UV and gamma-radiation. To identify epistatic interactions with members of the 4 Uvs groups, double mutants strains were isolated (Käfer and Chae 1994 Curr. Genet. 25:223-232). However, some mus;uvs double mutants could not be analyzed because they grew too poorly or were lethal (showing "synthetic enhancement in gene interaction"; Guarente 1993 Trends Genet. 9:362-366). The opposite effect was also found; namely interaction which led to improved recovery and growth (or "rescue") as documented here.